ELECTRONIC TURN IS THE RESULTING COMPLEX OF THE IMPLEMENTATION OF THE PRINCIPLES OF THE ELECTRONIC GOVERNANCE - Kravets R.B.; Romaniv Т.М. (Pressing Problems of Public Administration, 2018)
The article explores the stages of development of e-government in Ukraine. The advantages of theelectronic queue system for the organizations providing services are described, and it is describedwhat services can be used through electronic services. It describes the elements from which theelectronic queue and the scope of application take place.